The prevalence of pediculus capitis among the middle schoolchildren in Fars Province, southern Iran - Davarpanah, Mohammad Ali (Babol University of Medical Sciences, 2013)
Background: Pediculosis capitis is a common parasitic infection of children. In this study we assessed the prevalence of head pediculosis among the middle schoolchildren in the urban and rural areas of Fars province, southern Iran. Methods: All middle schoolchildren ages 11-14, in all the urban and rural areas of the province were screened for head lice infestation by examining their hair and scalp. The parents of the infested children were also examined. The study was repeated in the different seasons in the same areas. Moreover, the infested children were treated with permethrin shampoo and re-examined one week later for any relapse. Results: The general prevalence of head lice infestation in middle school students was 0.23% in autumn, 0.27% in winter and 0.11% in spring. In all three seasons, pediculosis capitis prevalence was higher among females and in the rural areas. Treatment with permethrin shampoo was markedly more successful in males from both regions in all months except the urban areas in spring. Conclusion: The results show that pediculus capitis is generally uncommon among Fars Province middle schoolchildren. It is needed that health providers promote heath education programs especially in the rural areas.